2
$\begingroup$

I have been trying to prove that $$ \lim\limits_{x\to \infty} (1+\frac{1}{\ln x})^x = \infty $$ and this is what I got: $$ \lim\limits_{x\to \infty} (1+\frac{1}{\ln x})^x = \lim\limits_{x\to \infty} e^{\ln (1+\frac{1}{\ln x})^x} = \lim\limits_{x\to \infty} e^{x * \ln (1+\frac{1}{\ln x})} $$ Then due to the fact that the e function is continuous and that $a*b=\frac{a}{\frac1b}$ $$ = e^{ \lim\limits_{x\to \infty} \frac{\ln (1+\frac{1}{\ln x})}{\frac1x} } $$ Since both the top and the bottom go to 0 as ${x\to \infty}$ we can apply L'Hospital and after deriving both we get $$ e^{ \lim\limits_{x\to \infty} \frac{-\frac{1}{x*\ln x+x*\ln^2 x}}{-\frac{1}{x^2}}} = e^{ \lim\limits_{x\to \infty} \frac{x^2}{x*(\ln x+\ln^2 x)}} = e^{ \lim\limits_{x\to \infty} \frac{x}{\ln x+\ln^2 x}} $$ and then since the x function grows much more rapidly than the logarithmic functions at any power, we get $$ e^{ \lim\limits_{x\to \infty} \frac{x}{\ln x+\ln^2 x}} = e^{\infty} = \infty $$ Since I am quite new to calculus I don't feel sure at all about what I just did so it would be great if I could get some feedback from experienced people. Also it's my first post here, I hope I didn't break any rule. In the meantime, I wish everyone a nice day.

$\endgroup$
  • $\begingroup$ This is correct, so far as I can see, and the post is fine. +1 I would suggest writing $f(x) = \ln{(1+1/\ln{x})}^x$ and evaluating $\lim_{x\to\infty}f(x),$ though. That way you get rid of all those exponentials, and it easier to read. Once you find that the limit is $\infty$ you know the limit you seek is $e^\infty.$ The difference from what you did is mainly typographical. $\endgroup$ – saulspatz Mar 9 at 17:49
3
$\begingroup$

This limit is equal to $$\lim_{x\to\infty} \bigg(\big(1+\frac{1}{\ln{x}}\big)^{\ln{x}}\bigg)^{(\frac{x}{\ln{x}})}=e^{\lim_{x\to\infty}\frac{x}{\ln{x}}}=e^{\infty}=\infty$$

$\endgroup$
  • $\begingroup$ Thank you very much. So the fact the logarithmic function grows slowlier than the simple x is generally accepted and does not need particular other proofs, I assume. $\endgroup$ – Luca Ricchi Mar 9 at 17:43
  • $\begingroup$ One can use L'Hôpitals rule to prove this limit is infinite. $\endgroup$ – Peter Foreman Mar 9 at 17:44
  • $\begingroup$ Can you accept my solution? $\endgroup$ – Peter Foreman Mar 9 at 18:03
  • $\begingroup$ of course, I find it very elegant, thanks again but I can't upvote because I am new and I still don't have 15 points of reputation $\endgroup$ – Luca Ricchi Mar 9 at 18:05
0
$\begingroup$

Taking $\log$ :

$f(x):=$

$x (\log (1+\dfrac{1}{\log x})-\log 1)=$

$(\dfrac{x}{\log x})\dfrac{\log (1+\dfrac{1}{\log x})-1}{\dfrac{1}{\log x}}.$

Set $h:=\dfrac{1}{\log x}$:

$x \rightarrow \infty$ implies $h \rightarrow 0^+$.

$\lim_{ h \rightarrow 0^+}\dfrac{\log (1+h)-1}{h}=$

$ \log '(1)=1.$

Hence for small enough $h$:

$\dfrac{\log (1+h)-1}{h} >1/2.$

For large enough $x$:

$(1/2)\dfrac{x}{\log x}< f(x)$, i.e not bounded above.

Exponentiate and take the limit $x \rightarrow \infty.$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.